IN VITRO ESTABLISHMENT OF KAPOK TREE (Ceiba pentandra L. Gaertn) APICAL SHOOTS - SILVA, Perla Pimentel da; CONTIM, Luis Antônio Serrão; FREITAS, Danival Vieira de; ARIDE, Paulo Henrique Rocha; SANTOS, André Luis Wendt dos (Scientia Agraria, 2010)
The kapok tree (Ceiba pentandra L. Gaertn) is a forest species with high importance to the forest sector in North of Brazil. Despite of that, there are no reports about the in vitro culture of this species. The aim of this work was the development of a reliable protocol for disinfestation and in vitro culture of apical shoots of kapok tree. There were tested different chemical compounds (NaOCl, HgCl2 e AgNO3) for apical shoot disinfestation and in vitro establishment. Different types and concentrations of citokinins (BAP, CIN e TDZ) were tested during apical shoot rooting, elongation, and bud induction. Although forest species are normally considered difficult to establish and cultivated in vitro, the kapok tree did not show problems during in vitro manipulation.